EXPLORING THE ADOLESCENTS’ ATTITUDE TOWARDS JUNK FOOD IN TIRUVANNAMALAI - Shafiullah, S.; Sivakumar, R. (International Journal of Research -GRANTHAALAYAH, 2021)
The term fast food or as referred as the junk food is the food which can be served immediately for eating. Sausages, hamburgers and pizzas come under the category of fast food or the junk food. It can be otherwise said that junk food and fast food are used as synonyms. These junk foods are inherent with a high level of energy with high content of sugar, salt and fat. On the contrary, these types of food have the characteristics of low nutritious level with low level of protein, low level of vitamin, low fibre content as well as low level of minerals. The definition for junk food had been given as the foods which are prepared earlier then served or the ones which are prepared immediately for serving. In this context, the current research study has been done to analyse the adolescent’s attitude towards the junk foods. The study has been carried out the junk food consumers in Tiruvannamalai. The respondents of the study are selected through convenience sampling and the sample size is fixed at 100. Questionnaire is the instrument used to collect the information for the study. The collected data is put into analysis through the technique of mean score. The result of the study shows that most of adolescents like the taste of junk food.